Fatal Calf Pneumonia Outbreaks in Italian Dairy Herds Involving Mycoplasma bovis and Other Agents of BRD Complex - Fanelli, Angela; Cirilli, Margie; Lucente, Maria Stella; Zarea, Aya Attia Koraney; Buonavoglia, Domenico; Tempesta, Maria; Greco, Grazia (Frontiers in Veterinary Science, 2021)
Mycoplasma bovis is worldwide increasingly recognized as an important cause of disease with major welfare and production impairments on cattle rearing. Although it was detected in veal calves and beef cattle, little is known on the infection impact and on its temporal morbidity pattern in Italian dairy herds. Thus, this study aimed to investigate the involvement of M. bovis in fatal calf pneumonia outbreaks that occurred during 2009-2019 in 64 Italian dairy farms. Besides, for a deeper diagnostic workup concurrent infection with other viral and bacterial respiratory pathogens was assessed. Out of the investigated fatal pneumonia cases, M. bovis was frequently detected (Animal Prevalence: 16.16%, 95%CI: 11.82-21.33, Herd Prevalence: 26.56, 95%CI: 16.29-39.08) either as the single agent of the disease in more than half of the positive samples (20/37), or in concurrent infections with Histophilus somni (9/37, 24.3%), Mannheimia haemolytica (6/37, 16.621%), Trueperella pyogenes (1/37, 2.70%), Pasteurella multocida (1/37, 2.70%), Bovine respiratory syncytial virus (5/37, 13.51%) and Bovine viral diarrhea virus (2/37, 5.55%). Based on time-series analysis, M. bovis was recorded in the area since 2009 with outbreaks displaying a clear morbidity seasonal pattern with peaks in April (43.21%) and in September (13.51%). This might be due to the stressing conditions during spring and late summer periods. Results of this study highlight that M. bovis infection is of warrant consideration, and control measures are needed given its involvement in lethal pneumonia outbreaks in dairy herds from an extended area.